2021
DOI: 10.1021/acs.organomet.1c00245
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Dehydrocoupling of Amines and Silanes Catalyzed by Magnesocenophanes

Abstract: The application of C[1]magnesocenophanes in dehydrocoupling catalysis is reported. Two new cycloalkylidenebridged C[1]magnesocenophanes were synthesized and structurally characterized. These C[1]magnesocenophanes were used as catalysts in amine−borane dehydrocoupling and, more extensively, in amine−silane cross-dehydrocoupling. The substrate scope, involving different aliphatic, aromatic, and benzylic amines, was probed and the mechanism of this cross-dehydrocoupling catalysis was investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 49 publications
3
29
0
Order By: Relevance
“…Literature known ansa-half-sandwich ligands [50][51][52][53] were reacted with dibutylmagnesium to obtain the corresponding ansa-halfsandwich magnesium complexes 1 a-d (Scheme 1). Similar to magnesocenophanes, [24,25,[54][55][56] 1 a-d possess Lewis acidic magnesium atoms and crystalized as solvent adducts from donor solvent (Figure 1, S14-S18). In case of 1 a-c, mono dme adducts are observed in the solid state, with the dme molecule coordinated to the magnesium atom via both oxygen atoms and the magnesium atom exhibiting an η 5 coordination mode to the Cp group.…”
Section: Synthesis and Characterization Of Ansa-half-sandwich Magnesi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Literature known ansa-half-sandwich ligands [50][51][52][53] were reacted with dibutylmagnesium to obtain the corresponding ansa-halfsandwich magnesium complexes 1 a-d (Scheme 1). Similar to magnesocenophanes, [24,25,[54][55][56] 1 a-d possess Lewis acidic magnesium atoms and crystalized as solvent adducts from donor solvent (Figure 1, S14-S18). In case of 1 a-c, mono dme adducts are observed in the solid state, with the dme molecule coordinated to the magnesium atom via both oxygen atoms and the magnesium atom exhibiting an η 5 coordination mode to the Cp group.…”
Section: Synthesis and Characterization Of Ansa-half-sandwich Magnesi...mentioning
confidence: 99%
“…Recently, we demonstrated that [1]magnesocenophanes are potent catalysts in the dehydrocoupling of amine-boranes. [24,25] While many magnesium based catalysts require elevated temperatures to operate, [26][27][28][29] [1]magnesocenophanes were able to catalyze the dehydrocoupling reactions of different dialkylamine-boranes at room temperature. [24,25] We therefore started our investigations into the catalytic abilities of ansa-halfsandwich magnesium complexes 1 a-d by testing their performance in the dehydrocoupling of amine-boranes.…”
Section: Amine-borane Dehydrocouplingmentioning
confidence: 99%
“…In 2021, the Scha ¨fer group reported the first example of C [1]magnesocenophanes for the dehydrogenative coupling of amines with silanes. 37 There was limited reactivity with this catalytic system and better conversions and selectivity were obtained when amine was coupled with diphenylsilane as compared to phenylsilane.…”
Section: Alkali and Alkaline Earth Metalsmentioning
confidence: 99%
“…The dehydrocoupling between amines and hydrosilanes seems to be the most attractive route, due to the formation of H 2 as the by-product (Figure 1, c). [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Unfortunately, this approach is completely impractical for the preparation of a highly important trimethylsilyl-protecting group, due to the pyrophoricity of gaseous Me 3 SiH. Moreover, the control of the chemoselectivity for Si-H/N-H dehydrocoupling has proved to be challenging due to the possible formation of several products including polymeric silazanes and a mixture of mono-and di-silylated amines.…”
mentioning
confidence: 99%
“…1c). [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Unfortunately, this approach is completely impractical for the preparation of a highly important trimethylsilyl-protecting group, due to the pyrophoricity of gaseous Me 3 SiH. Moreover, the control of the chemoselectivity for Si-H/N-H dehydrocoupling has proved to be challenging due to the possible formation of several products including polymeric silazanes and a mixture of mono-and disilylated amines.…”
mentioning
confidence: 99%